ANALISIS USAHA PEMBENIHAN IKAN PATIN DI KECAMATAN SEBERIDA KABUPATEN INDRAGIRI HULU PROVINSI RIAU (Studi Kasus Pada BBI Pangkalan Kasai) - Cindy Amalia Putri; Tibrani (DINAMIKA PERTANIAN, 2023)
This study aims to analyze the characteristics and profile of hatchery workers at BBI Pangkalan Kasai, Seberida District, Indraguri Hulu Regency, Hatchery Technology and Availability of Production Facilities in Catfish Hatchery Business at BBI Pangkalan Kasai, Seberida District, Indraguri Hulu Regency, and Production Cost, Income, Profit, Business Efficiency, and Break Event Point (BEP) in Catfish Hatchery Business at BBI Pangkalan Kasai, Seberida District, Indragiri Hulu Regency. This research uses the case study method. Research at BBI Pangkalan Kasai in Seberida District, Indragiri Hulu Regency, Riau Province was carried out from April to September 2022. The respondents in this study were 10 people, consisting of 1 head of the UPTD Fish Seed Center, 2 employees of the administration section, 1 seed gatherer, and 6 technical personnel. The data used is primary and secondary. The data analysis methods used are descriptive, qualitative, and quantitative. The results showed that: (1) The average age of hatchery workers is 35 years, the average length of education is 12 years or is at the upper secondary level; the average hatchery experience is 4.3 years; and the average number of dependents in an entrepreneur's family is on average 3.3. The BBI Pangkalan Kasai profile was originally established in 2000 and had a land area of about 4 hectares. The organizational structure of BBI Pangkalan Kasai consisted of the Head of UPTD BBI Pangkalan Kasai, Ka. Sub. Ch. Administration, Seed Pramu, Technical Staff, Administrative Staff, Cleaning Staff, and Security Guard, Business capital is fully sourced from the Department of Fisheries of Indragiri Hulu Regency. (2) The technology for catfish hatchery cultivation at the Pangkalan Kasai Fish Seed Center (BBI) was not in accordance with theoretical recommendations, ranging from broodstock storage, brood selection, injection mating, growth, egg hatching, larval storage, seed maintenance in a closed room, and harvesting, which has not been effective and efficient. Meanwhile, the availability of production facilities was adequate, starting with equipment and buildings, catfish broodstock, feed, medicines, and labor. (3) Analysis of catfish hatchery business at BBI Pangkalan Kasai: the production cost was Rp. 25.991.834/production process, the gross income obtained by BBI Pangkalan Kasai was Rp. 70.000.000/production process, the net income is Rp. 44.008.166/production process, and the business efficiency was 2,69. BEP value of Rp. 4.183,33/head, BEP unit of 31.100,2 BEP price of 74,3 head.